Implementation of Digital Campaign in Ranca Upas for Sustainable Tourism - Desy Oktaviani; Keni Kaniawati; Andhi Sukma (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
The concept of a sustainable tourism campaign has the content of environmental awareness activities that are made in such a way as to attract tourists as well as content to promote the sustainability of a tourist destination. With today's lifestyle that cannot be separated from technology, the campaign concept involves a lot of digital media to contribute to the wider community. One of the tourism sites that has the potential to develop sustainable tourism is Ranca Upas. The purpose of this study is to find out the application of digital campaigns and their benefits for sustainable tourism in Ranca Upas. This study utilizes qualitative analysis by using the construction of basic dimensions from previous researchers regarding digital campaigns and sustainable tourism. The results of the study show that the implementation of digital campaigns in Ranca Upas has not been maximized, but tourists' awareness of the benefits and existence of digital campaigns in Ranca Upas and its sustainable tourism program has a very good view. The implication of the research is expected to increase the effectiveness of the digital campaign structure in Ranca Upas which is expected to have an impact on tourists' awareness of the organized digital campaign and the importance of sustainable tourism.